Digital ta’aruf and gender identity: A study of gender performativity - Tania, Elsa (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: The phenomenon of online taaruf has emerged as an alternative method of finding a spouse in the digital age, widely used by Muslim youth. Its scope in the virtual world has brought this phenomenon into new dynamics in gender relations, differing from traditional taaruf. Methods: Through qualitative methods by interviewing 13 informants and using NVivo as a data analysis tool, as well as gender performativity theory, this study aims to explore the performance and expectations of gender roles during online taaruf, their changes after marriage, as well as participants' views on polygamy and how gender differences influence differing perspectives on such practices. Findings: The findings of this study indicate that women tend to present a feminine image, capable of performing domestic tasks, and patient. Meanwhile, men more often showcase leadership, responsibility, and authority. Conclusion: This study concludes that online taaruf reinforces traditional gender roles based on religious norms, where there is an imbalance of authority between men and women. These findings emphasize the urgency of gender-based digital literacy. Novelty/Originality of this article: The novelty of this study lies in applying gender performativity theory to understand how participants in digital taaruf perform and negotiate their gender roles, how these performances shift after marriage, and how gender differences shape perceptions of polygamy in the digital era.